Climatic CO2 level-driven changes in the bioavailability, accumulation, and health risks of Cd and Pb in paddy soil–rice systems. (1st May 2023) - Wang, Yabo; Wang, Xiaojie; Ai, Fuxun; Du, Wenchao; Yin, Ying; Guo, Hongyan
Abstract: Rising atmospheric carbon dioxide (CO2 ) and soil heavy metal pollution, which affects safe rice production and soil ecosystem stability, have caused widespread concern. In this study, we evaluated the effects of elevated CO2 on Cd and Pb accumulation in rice plants ( Oryza sativa L.), Cd and Pb bioavailability, and soil bacterial communities in Cd–Pb co-contaminated paddy soils via rice pot experiments. We showed that elevated CO2 accelerates the accumulation of Cd and Pb in rice grains by 48.4–75.4% and 20.5–39.1%, respectively. Elevated CO2 levels decreased soil pH value by 0.2 units, which increased Cd and Pb bioavailability in soil but inhibited iron plaque formation on rice roots, ultimately promoting Cd and Pb uptake. 16S rRNA sequencing analysis revealed that elevated CO2 increased the relative abundance of certain soil bacteria (e.g., Acidobacteria, Alphaproteobacteria, Holophagae, and Burkholderiaceae). A health risk assessment showed that elevated CO2 markedly increased the total carcinogenic risk values for children, adult males, and adult females by 75.3% ( P  < 0.05), 65.6% ( P  < 0.05), and 71.1% ( P  < 0.05), respectively. These results demonstrate the serious performance of elevated CO2 levels in accelerating the bioavailability and accumulation of Cd and Pb in paddy soil–rice ecosystems, with particular risks for future safe rice production. Graphical abstract: Image 1 Highlights: Elevated CO2 increased Cd and Pb bioavailability in Cd–Pb co-contaminated paddy soil. Elevated CO2 decreased soil pH and iron plaque formation. Elevated CO2 mitigated the negative effects of Cd–Pb on soil bacteria. Elevated CO2 exacerbated the human health risks of rice Cd–Pb pollution.